Adding a construction sector to COSMO: Structure and policy analysis - Paul Egan; Adele Bergin (The Economic and Social Research Institute (ESRI), 2022)
This paper outlines the newly developed construction sector which has been incorporated into the ESRI's macroeconometric model, COSMO. Given the importance of the construction sector to the Irish economy, incorporating specific relationships for production, employment and wages in the sector provides more realistic linkages between the activity of the real economy and financial sector. This paper presents the econometric structure of the new construction sector by describing the data and key equations used to estimate the relevant variables. It also examines the key interlinkages between the construction sector, the financial block and the real economy. Finally, the paper presents the model's scenario capabilities by illustrating a number of shocks. These include policy type shocks which examine the potential impact of increases in government spending, as well as more sector specific shocks such as changes in the number of housing completions, the cost of building materials and changes in construction sector employment.
Keywords: 330